Response of integrated nutrient management on growth, seed yield and economics of sesame (Sesamum indicum L.) under rainfed conditions in sub montane Punjab: RESPONSE OF INM ON GROWTH, SEED YIELD AND ECONOMICS OF SESAME IN SUB MONTANE PUNJAB - VIVEK SHARMA; M J SINGH; VIJAY KUMAR; ANIL KHOKHAR (Journal of Oilseeds Research, 2018)
Experiment was conducted during kharif 2014 and 2015, under rainfed conditions using sesame cv. RT 346, in sandy loam soil at Regional Research Station (Punjab Agricultural University) Ballowal Saunkhri, SBS Nagar District, Punjab. The aim of the study was to assess the effect of different levels of N, P and K on seed yield, nutrient uptake and agronomic efficiencies in sesame. The experiment was laid out in randomized block design with 6 treatments viz., Control, 35:0:0 (basal dose), 35:0:0 (basal dose) + 10 ton FYM/ha, 70:0:0 (2 N splits), 70:40:0 (2 N splits), 70:40:15 (2 N splits). Among the different treatments, application of NPK as 70:40:0 with nitrogen in two splits recorded the maximumvalues for growth parameters viz., plant height, number of branches per plant and yield attributes viz., number of capsules plant per plant and number of seeds capsule per capsule and this treatment was at par with application of NPK as 70:0:0 treatment (2 N splits) and 35:0:0+10 ton FYM/ha treatment. Highest average seed yield of 852 kg/ha was recorded with treatment 70:40:0 with nitrogen in two splits which was 44 per cent higher over the control treatment. The nitrogen, phosphorus and potassium uptake was also highest in the treatment NPK 70:40:0 followed by 70:0:0 and 35:0:0 + 10t/ha FYM, which was significantly higher over the control treatment. The net return (` 42,545) and B:C ratio (3.34) was also highest in the treatment 70:40:0 as compared to the other treatments.